EMRP project MetroMetal: selected results of ENVINET and CMI - Tecl, J; Solc, J; Kovar, P; Buňata, Milan (Radiation protection dosimetry, 2014)
Within the framework of the European Metrological Research Program (EMRP) IND04 MetroMetal 'Ionizing radiation metrology for the metallurgical industry', joint research carried out by 14 metrological institutions from countries within the European Union and the company ENVINET, questions concerning the determination of radioactivity in samples relevant to the metallurgical industry were resolved. The results of project tasks, namely questionnaire, composite standards development and samples from metallurgical industry measurement, are presented here.
Keywords: biomedicínský výzkum; Radiation Monitoring; Research Design; průzkumy a dotazníky; Radiation Protection; Surveys and Questionnaires; lidé; Occupational Exposure; Industry; Evropská unie; hutnictví; Metallurgy; monitorování radiace; průmysl; pracovní expozice; European Union; radiační ochrana; Biomedical Research; výzkumný projekt; Humans